1994
DOI: 10.1046/j.1468-2982.1994.1401021.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Platelet Mitochondrial Function in Patients Affected by Migraine With and Without Aura

Abstract: To investigate energy metabolism in migraine, we determined platelet mitochondrial enzyme activities in 40 patients with migraine with aura and in 40 patients with migraine without aura during attack-free intervals and in 24 healthy control subjects. NADH-dehydrogenase, citrate synthase and cytochrome-c-oxidase activities in both patient groups were significantly lower than in controls (p < 0.01), while NADH-cytochrome-c-reductase activity was reduced only in migraine with aura (p < 0.01). No alteration in suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 11 publications
0
53
0
1
Order By: Relevance
“…Platelet mitochondrial enzyme activities were found significantly lower in MwoA patients than in controls (53). Plasma lactate and pyruvate levels were found significantly increased in migraine patients compared to controls (54).…”
Section: Resultsmentioning
confidence: 71%
“…Platelet mitochondrial enzyme activities were found significantly lower in MwoA patients than in controls (53). Plasma lactate and pyruvate levels were found significantly increased in migraine patients compared to controls (54).…”
Section: Resultsmentioning
confidence: 71%
“…Our more recent data has demonstrated the same strong maternal inheritance bias in CVS cases without coexisting neuromuscular disease [Boles et al, submitted for publication to Am J Med Genet]. Other data supporting a mtDNA component in the pathogenesis of migraine headache and CVS include lactic acidosis in both conditions [Montagna et al, 1988;Okada et al, 1998;Boles et al, 2003a], energy depleted urine organic acid metabolite profiles in CVS [Boles and Williams, 1999;Boles et al, 2003a]; decreased oxidative phosphorylation activities in both conditions [Montagna et al, 1988;Sangiorgi et al, 1994;Boles et al, 2003a], and reduced in vivo brain phosphocreatine to inorganic phosphate ratio by 31 P magnetic resonance spectroscopy in migraine headache [reviewed in Montagna et al, 1994].…”
Section: Introductionmentioning
confidence: 58%
“…Histological studies have revealed ragged-red fibers and cytochrome-c-oxidase-negative fibers in skeletal muscle of patients with migraines with prolonged aura (7,53). Biochemical studies and imaging studies have demonstrated decreased activity in the ETC complexes and metabolic abnormalities of patients with migraines (7,44,55). Increased plasma lactate levels and impaired brain oxidative energy metabolism have been observed in migraineurs during and between migraine attacks (36,47).…”
mentioning
confidence: 99%